Defying transparency: Ghostwriting from the Jazz Age to social media. (March 2021) - Carvalho, John; Chung, Angie; Koliska, Michael
Ghostwriting became a popular practice in sports journalism during the 1920s, as championed by sports press agent Christy Walsh. The practice has re-emerged in the 21st century, in social media and particularly as demonstrated by the new website The Players' Tribune. Its popularity encourages ethical discussion about ghostwriting's conflation of journalism and public relations, and the ethical debate it incites. Particular attention centers on the core journalism value of transparency, as it relates to both professions. The article posits that the blurring of professional boundaries between public relations and journalism can have detrimental effects to the credibility of both fields. The authors call for greater transparency in the use of ghostwriting, particularly when used in a sports journalism setting.